A study of methods to mitigate farm income fluctuations with special reference to taxation measures in selected countries - Lamont, Michael Peter (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1982.